Pengaruh Program Keluarga Harapan (PKH) Terhadap Kesejahteraan Masyarakat di Desa Oesoko Kecamatan Insana Utara Kabupaten TTU - Akoit, Fransiska L.M.B; Tameno, Nikson; Molidya, Aldarine (Universitas Pahlawan Tuanku Tambusai, 2024)
This research aims to determine the influence of the Family Hope Program (PKH) on community welfare in Oesoko Village, North Insana District, TTU Regency. The data used in this research includes primary and secondary data, which were analyzed using qualitative descriptive analysis methods. Data collection techniques were carried out through interviews, observation and documentation using Lawrence Green's theory. The research results show that the influence of PKH in Oesoko village is not optimal based on three welfare indicators. In accordance with Lawrence Green's theory, which consists of first, education, which is indicated by the use of aid funds by aid recipients for other purposes, not for educational needs. Second, the health of aid recipients has improved as seen from the development of the nutritional status of children in Oesoko village which has become better and also that pregnant women have found it easier to access health services. Third, income, which means the PKH assistance funds received cannot increase the KPM's income but can help reduce monthly expenses.